2022
DOI: 10.3390/agriculture12010056
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Design of a Pneumatic Wheat-Shooting Device Based on Numerical Simulation and Field Test in Rice–Wheat Rotation Areas

Abstract: In rice–wheat rotation areas of China, traditional wheat seeders have severe blockage, low working efficiency and poor seeding quality. In this study, a pneumatic shooting technology was designed, consisting mainly of a nozzle, shell and acceleration tube. To improve the sowing depth of the pneumatic shooting device, the response-surface methodology of structure parameters and CFD simulation technology was adopted in this work. The effects of working pressure, acceleration-tube diameter and throat distance on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Th matic wheat-shooting device had a faster and more stable airflow field after the o tion. Results of the field test showed that the optimized pneumatic wheat-shootin had about 68% higher seeding depth than the initial device [10]. Yazgi et al evaluated seed trajectories in different seed tubes.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Th matic wheat-shooting device had a faster and more stable airflow field after the o tion. Results of the field test showed that the optimized pneumatic wheat-shootin had about 68% higher seeding depth than the initial device [10]. Yazgi et al evaluated seed trajectories in different seed tubes.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…(Kang et al, 2015) optimized the original belt-type seed guide device through bench tests and improved its seeding quality. (Wang et al, 2020 a) designed a pneumatic wheat precision seed casting device. Through fluent simulation analysis to determine the key component parameters, and the test-bad shows the device can achieve accurate and stable single seed sowing.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, by analyzing the accelerating process of wheat seeds inside the seed discharger and the seed casting process, the seeding performance of the device was investigated, to obtain the factors that affect the wheat seeding effect [8]. Wang et al [9][10][11] proposed a non-contact pneumatic WRS seeding technology. After analyzing the injection speed required for qualified seeding under soil conditions with different water contents through bench tests, a WRS seeding device with high-pressure accelerating airflow was designed; subsequently, the characteristics of the airflow field and the influence relationship of various structural parameters on sowing quality were analyzed based on CFD techniques, and the key parameters of the seeding device were optimized.…”
Section: Introductionmentioning
confidence: 99%